mHealth in Practice Mobile Technology for Health Promotion in the Developing World - Donner, Jonathan; Mechael, Patricia (Bloomsbury Academic, 2012)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. There has recently been an explosion of interest around the application of mobile communication technologies to support health initiatives in developing countries (mHealth). As a result, there is a need to promote and share rigorous research for better informed policy, programming, and investment. There are, however, few platforms for the exchange of information and proven practice between practitioners and researchers. The subtopic of prevention, well-being, and health promotion within mHealth is particularly ripe for deeper exploration. While many reports tout the potential of mobiles to influence behaviour change for health, there is limited knowledge about what works (and what does not work), and about how to evaluate current and future programs. This is a focused edited volume with contributions from leading researchers and practitioners to identify best practices in using mobile technologies to promote healthy behaviours (and reduce unhealthy ones) in resource-constrained settings with a special focus on developing countries. This topic is inherently interdisciplinary. Though the opportunities to leverage mobile phones for health are new, the challenges confronting researchers and practitioners are well-established and theoretically complex, with roots in decades of work on mediated behaviour change campaigns and theories.